A GIS-based tool for the management of industrial accidents triggered by volcanic ash fallouts. Issue 2 (7th February 2016) - Ancione, Giuseppa; Salzano, Ernesto; Maschio, Giuseppe; Milazzo, Maria Francesca
Abstract : In this last decade, worldwide attention has been focused on the hazards derived from the interaction between extreme natural phenomena and critical infrastructures and/or chemical and process industry (natural–technological hazards or Na-Tech). Due to the recent occurrence of significant events, great attention has also been given to Na-Tech hazards triggered by volcanic eruptions; in particular, the eruption of the Icelandic volcano alarmed the European community due to the ash fallout over the continent, which caused significant problems for the population, road, rail and air traffic and production activities. This study aims at defining a procedure for the representation of the vulnerability of industrial facilities to potential volcanic ash fallouts. Its implementation on a Geographical Information System has also been executed and a semi-automatic procedure for the vulnerability mapping has been constructed.